The Relationship between Knowledge and Nutritional Status with the Incidence of Pneumonia in Toddlers at the Medika Utama Manggar Hospital, Balikpapan - Rahma, Rahmatika; Zulaikha, Fatma (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Pneumonia is an infectious disease that often affects toddlers due to low immunity, one of which is caused by poor nutrition, so their nutritional status is lacking. The lack of knowledge of mothers, aKnowledgemonia and the lack of proper dietary intake for toddlers can cause this. This study aims to determine the relationship between knowledge and nutritional status and pneumonia incidence in toddlers at the Medika Utama Manggar Balikpapan Hospital. The research design was quantitative, using a correlation research type with a cross-sectional approach. The population of mothers and toddlers treated at the Medika Utama Manggar Balikpapan Hospital who were treated from October to December 2023 was 152 toddlers. The sampling technique was Purposive Sampling with the Slovin formula, which obtained 116 respondents. The data was analyzed using the Spearman Rank. The results obtained were a relationship between knowledKnowledgee incidence of pneumonia (p-value = 0.004) with a correlation of 0.266 (low relationship) and a positive relationship direction. In the nutritional status variable, there is a relationship between nutritional status and the incidence of pneumonia (p-value = 0.000) with a correlation of 0.354 (low relationship) and a positive relationship direction. It can be concluded that the incidence of pneumonia in toddlers can be caused by the lack of knowledge on how to treat pneumonia and the low nutritional status of toddlers. The recommended suggestion is that mothers increase their knowledge to fulfill children's nutrition needs according to their growth and development.